Resolving ambiguities in nanowire field-effect transistor characterization. Issue 43 (20th October 2015) - Heedt, Sebastian; Otto, Isabel; Sladek, Kamil; Hardtdegen, Hilde; Schubert, Jürgen; Demarina, Natalia; Lüth, Hans; Grützmacher, Detlev; Schäpers, Thomas
Abstract : The profound impact of InAs nanowire surface states on transistor functionality is quantified using a novel dual-gate FET evaluation method in conjunction with finite element method simulations of nanowire electrostatics. Abstract : We have modeled InAs nanowires using finite element methods considering the actual device geometry, the semiconducting nature of the channel and surface states, providing a comprehensive picture of charge distribution and gate action. The effective electrostatic gate width and screening effects are taken into account. A pivotal aspect is that the gate coupling to the nanowire is compromised by the concurrent coupling of the gate electrode to the surface/interface states, which provide the vast majority of carriers for undoped nanowires. In conjunction with field-effect transistor (FET) measurements using two gates with distinctly dissimilar couplings, the study reveals the density of surface states that gives rise to a shallow quantum well at the surface. Both gates yield identical results for the electron concentration and mobility only at the actual surface state density. Our method remedies the flaws of conventional FET analysis and provides a straightforward alternative to intricate Hall effect measurements on nanowires.